Addressing Suicide in the Veteran Population: Engaging a Public Health Approach - Carroll, David; Kearney, Lisa K.; Miller, Matthew A. (Frontiers in Psychiatry, 2020)
Suicide is a national public health issue in America, and it disproportionately affects those who are serving or who have served in the United States military. The US Department of Veterans Affairs (VA) has made suicide prevention its number one clinical priority. VA is committed to prevent suicide among the entire population of those who have served our country in the military, regardless of whether they make use of any VA services or benefits. Suicide can be prevented through the application of a public health strategy embracing partners at all levels. Following a national strategy, VA has embarked on an effort involving the application of a public health strategy combining both clinically-based and community-focused interventions. This paper describes several examples of these efforts and the pathway forward.